The impact of the Belt and Road Initiative on green innovation and innovation modes: empirical evidence from Chinese listed enterprises - Li, Bowen; Zhang, Zijing; Zhang, Zhaoyong (Frontiers in Environmental Science, 2024)
Under the Belt and Road Initiative (BRI), promoting green innovation in enterprises has been the central focus of the developmental strategy for China and countries along the Belt and Road to ensure sustainable development in line with the UN Sustainable Development Goals (SDGs) related to the environment and development. This paper examines the driving factors and heterogeneous mechanisms of the BRI in green technology innovation, especially in collaborative vs. independent innovation modes, utilizing a multi-period difference-in-difference model (DID) and micro-level panel data of Chinese listed enterprises spanning from 2007 to 2021. We find that the BRI has significantly stimulated the number of green innovations of participating enterprises, primarily through the adoption of collaborative innovation mode, and the BRI policies are more likely to induce green innovation behavior of enterprises with high research and development (R&D), high quality of environmental information disclosure, and non-state-owned enterprises (SOEs), as well as in heavy-polluting industries. The implementation of the BRI has led to increased support from the government, financial institutions, and scientific research organizations to the participating enterprises, which helps alleviate their financial constraints and enhance patent transformation efficiency, and thus facilitate green innovation. These results are robust across different regression specifications. This study contributes to the existing literature on BRI’s environmental impact and green innovation with firm-level evidence, and has important policy implications for the Chinese government when promoting green innovation and internationalization of Chinese enterprises.